Toxoplasma-IgM and IgG-avidity in single samples from areas with a high infection rate can determine the risk of mother-to-child transmission Avidez de IgM e IgG de Toxoplasma em amostras de áreas com alta taxa de infecção pode determinar risco de transmissão materno-fetal - Myrian Morussi Reis; Maria Madalena Tessaro; Pedro Alves D'Azevedo (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
Anti-Toxoplasma IgG-avidity was determined in 168 serum samples from IgG- and IgM-positive pregnant women at various times during pregnancy, in order to evaluate the predictive value for risk of mother-to-child transmission in a single sample, taking the limitations of conventional serology into account. The neonatal IgM was considered the serologic marker of transmission. Fluorometric tests for IgG, IgM (immunocapture) and IgG-avidity were performed. Fifty-one of the 128 pregnant women tested gave birth in the hospital and neonatal IgM was obtained. The results showed 32 (62.75%) pregnant women having high avidity, IgM indexes between 0.6 and 2.4, and no infected newborn. Nineteen (37.25%) had low or inconclusive avidity, IgM indexes between 0.6 and 11.9, and five infected newborns and one stillbirth. In two infected newborns and the stillbirth maternal IgM indexes were low and in one infected newborn the only maternal parameter that suggested fetal risk was IgG-avidity. In the present study, IgG-avidity performed in single samples from positive IgM pregnant women helped to determine the risk of transmission at any time during pregnancy, especially when the indexes of the two tests were analysed with respect to gestational age. This model may be less expensive in developing countries where there is a high prevalence of infection than the follow-up of susceptible mothers until childbirth with monthly serology, and it creates a new perspective for the diagnosis of congenital toxoplasmosis. A avidez de IgG anti-Toxoplasma foi realizada em 168 amostras IgG e IgM positivas de gestantes, coletadas em qualquer período da gestação, para avaliar o valor preditivo do risco de transmissão materno-fetal em amostra única, considerando as limitações da sorologia convencional. A IgM neonatal foi considerada o marcador sorológico de transmissão. Testes fluorométricos foram realizados para IgG, IgM (imunocaptura) e avidez de IgG. Cinqüenta e uma das 128 gestantes testadas tiveram os partos realizados na instituição e a IgM ...